Comparative Genomics of Lactobacillus acidipiscis ACA-DC 1533 Isolated From Traditional Greek Kopanisti Cheese Against Species Within the Lactobacillus salivarius Clade - Kazou, Maria; Alexandraki, Voula; Blom, Jochen; Pot, Bruno; Tsakalidou, Effie; Papadimitriou, Konstantinos (Frontiers in Microbiology, 2018)
Lactobacillus acidipiscis belongs to the Lactobacillus salivarius clade and it is found in a variety of fermented foods. Strain ACA-DC 1533 was isolated from traditional Greek Kopanisti cheese and among the available L. acidipiscis genomes it is the only one with a fully sequenced chromosome. L. acidipiscis strains exhibited a high degree of conservation at the genome level. Investigation of the distribution of prophages and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPRs) among the three strains suggests the potential existence of lineages within the species. Based on the presence/absence patterns of these genomic traits, strain ACA-DC 1533 seems to be more related to strain JCM 10692T than strain KCTC 13900. Interestingly, strains ACA-DC 1533 and JCM 10692T which lack CRISPRs, carry two similar prophages. In contrast, strain KCTC 13900 seems to have acquired immunity to these prophages according to the sequences of spacers in its CRISPRs. Nonetheless, strain KCTC 13900 has a prophage that is absent from strains ACA-DC 1533 and JCM 10692T. Furthermore, comparative genomic analysis was performed among L. acidipiscis ACA-DC 1533, L. salivarius UCC118 and Lactobacillus ruminis ATCC 27782. The chromosomes of the three species lack long-range synteny. Important differences were also determined in the number of glycobiome related proteins, proteolytic enzymes, transporters, insertion sequences and regulatory proteins. Moreover, no obvious genomic traits supporting a probiotic potential of L. acidipiscis ACA-DC 1533 were detected when compared to the probiotic L. salivarius UCC118. However, the existence of more than one glycine-betaine transporter within the genome of ACA-DC 1533 may explain the ability of L. acidipiscis to grow in fermented foods containing high salt concentrations. Finally, in silico analysis of the L. acidipiscis ACA-DC 1533 genome revealed pathways that could underpin the production of major volatile compounds during the catabolism of amino acids that may contribute to the typical piquant flavors of Kopanisti cheese.